Managerial Economics: Foundations of Business Analysis and Strategy - Thomas Christopher.R (Mc Graw Hill, 2010)
The goal of Thomas and Maurice’s Managerial Economics has always been, and continues to be, to teach students the economic way of thinking about business decision and strategy. This edition continues to develop critical thinking skills and provides students with a logical way of analyzing both the routine decisions of managing the daily operations of a business as well as the longer-run strategic plans that seek to manipulate the actions and reactions of rival firms.